The production process of Cahaya Hikmah as a media content for Islamic propagation on the PWMU TV YouTube channel. - Adek Dharma Santoso (DIGICOM : Jurnal Komunikasi dan Media, 2023)
In this modern era, communication is one of the important factors for the progress of a nation. Communication that occurs can be through a medium both electronic and print. One of the electronic media that has been popular and very effective for delivering information and messages is television. With its various programs, television is able to provide information, education, entertainment and so on. The program is packaged in a good way to make it interesting for those who watch it. This research uses a qualitative study approach, with a descriptive analysis method. descriptive method as a method that only describes situations and events, namely describing the actual situation. This research uses techniques in the form of interviews, data analysis conducted by researchers with parties who are directly involved with the research in question. The implication of this research is that the Cahaya Hikmah program is expected to be a religious program that is beneficial to the wider community, especially the Muhammadiyah citizens of East Java. In addition, the Cahaya Hikmah program is expected to be more innovative in optimizing the quality and production of its broadcasts. The researcher also hopes that other researchers will conduct in-depth research on the content of religious television programs, especially through Youtube social media, this social media in the millennial era has replaced the position of conventional television, so that in the future the quality of religious content can be better and produce more quality and useful shows.